İLK DÖNEM KUR’AN TASAVVURU VE DÖNÜŞÜMÜ -Kimlik ve Kitâb İlişkisi Bağlamında- - Selim Türcan (İslami İlimler Dergisi)
In early Islamic era, in mind of illiterate Arabs, there was a structural relation between the social self-image and between their Qur’an image. Arab social identity, was constructed on the contradiction between illiterate Arabs and the people of the scripture. Ka’bah was the central symbol. But Arabs were emulating their neighbours and they were desiring to achieve a scripture like them. This caused a big tension in their mind until Qur’an. When the Qur’an came, it was imagined as a suggestion about changing the settled illiterate social identity, its symbol and reference with a scripture. Politically, it caused a social split. After this identity stage, Arabs preferred the Qur’an/new scripture as base of identity. But this stage suggests for the new scripture an (even though it was being written) illiterate, valid, practical structure. The Prophet made The Qur’an felt and concealed by his self presence. In the last stage, when the Prophet (the concrete base of the identity and the scripture) died, illiterate muslim Arabs needed a literally standardized whole scripture. The Qur’an started to be imagined as an officially, wholly and literally concealed, and therefore unique valid scripture.